Ответы и объяснения

2012-10-26T22:41:48+04:00

{xy=y^x      (1)

{x^3=y^2     (2)

Из (2) получим х = у^(2/3)

Подставим в (1)

у^(2/3) ·y¹ = y^(у^(2/3))

у^(5/3) = y^(у^(2/3))

Приравниваем степени

5/3 = у^(2/3)

откуда

у  = (5/3)^ (3/2) или

у = √(5/3)³ или

у = (5/3)· √(5/3)

Вернёмся к системе

{xy=y^x      (1)

{x^3=y^2     (2)

Преобразуем уравнение (1)

х = (y^x):у

х =у^(x - 1)

Подставим в (2)

у^(3·(x - 1)) = у²

приравниваем степени

3х - 3 = 2

3х = 5

х = 5/3

Ответ: х = 5/3у = (5/3)· √(5/3)


 

решил.перепроверил. все правильно